Investigating Critical Levels of Dry Rotting of Yellow Yam (Dioscorea Cayenesis) Planing Material, the Benefits of Disinfesting the Heads of Pratylechus Coffeae and of After-Planing Nematicide Treatments - Wahab, Abdul H. (IICA, 2021)
38 Páginas.